2021
DOI: 10.1177/01461672211036602
|View full text |Cite
|
Sign up to set email alerts
|

Lockdown Lives: A Longitudinal Study of Inter-Relationships Among Feelings of Loneliness, Social Contacts, and Solidarity During the COVID-19 Lockdown in Early 2020

Abstract: We examine how social contacts and feelings of solidarity shape experiences of loneliness during the COVID-19 lockdown in early 2020. From the PsyCorona database, we obtained longitudinal data from 23 countries, collected between March and May 2020. The results demonstrated that although online contacts help to reduce feelings of loneliness, people who feel more lonely are less likely to use that strategy. Solidarity played only a small role in shaping feelings of loneliness during lockdown. Thus, it seems we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…In total, 8 studies reported loneliness means (Ahrens et al, n.d.; Fanari and Segrin, 2021 ; Groarke et al, 2021 ; Lee et al, 2020 ; Rumas et al, 2021 ; Saidur et al, 2021 ; Stevenson and Wakefield, 2021 ; van Breen et al, 2021 ). One study of reported the mean of loneliness in 23 countries( van Breen et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 8 studies reported loneliness means (Ahrens et al, n.d.; Fanari and Segrin, 2021 ; Groarke et al, 2021 ; Lee et al, 2020 ; Rumas et al, 2021 ; Saidur et al, 2021 ; Stevenson and Wakefield, 2021 ; van Breen et al, 2021 ). One study of reported the mean of loneliness in 23 countries( van Breen et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 8 studies reported loneliness means (Ahrens et al, n.d.; Fanari and Segrin, 2021 ; Groarke et al, 2021 ; Lee et al, 2020 ; Rumas et al, 2021 ; Saidur et al, 2021 ; Stevenson and Wakefield, 2021 ; van Breen et al, 2021 ). One study of reported the mean of loneliness in 23 countries( van Breen et al, 2021 ). Five studies reported the means in two waves, one paper reported it in three waves, one study reported the means in 8 waves, and one paper reported it in four waves (the paper with a report in 23 countries; each country was included in the analysis, separately).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, local crime events could have made participants more reluctant to answer items about mafia groups. However, it should also be considered that, in line with research employing the RI‐CLPM in other contexts (e.g., Osborne & Sibley, 2020; Liekefett et al., 2021; Van Breen et al., 2021), within‐person effects are typically smaller and less stable over time compared with between‐person effects, or those obtained by traditional CLPMs. Additional multi‐wave longitudinal studies employing a variety of different measures are needed to investigate further changes in adolescents’ perceptions of criminal groups.…”
Section: Discussionmentioning
confidence: 76%
“…In a white paper written through the COVID-19 Rapid Response Impact Initiative, Cammett and Lieberman stressed the importance of solidarity-promoting public messaging already in March 2020, emphasizing the central role of mass media and societal leaders in that context ( Cammett & Lieberman, 2020 ). Studies conducted in the early phases of the pandemic, as well as during and after lockdown measures, particularly referred to solidarity as a crucial concept to overcome the pandemic (e.g., Marzana et al, 2021 ; McCormick, 2020 ; Moss & Sandbakken, 2021 ; Peng & Berry, 2021 ; van Breen et al, 2021 ). Relatedly, there were repeated calls for global solidarity to overcome regional resource bottlenecks and for pandemic containment ( Jecker & Atuire, 2021 ; Zagefka, 2021 ).…”
Section: Theorymentioning
confidence: 99%